Case Report: Malignant Pheochromocytoma Without Hypertension Accompanied by Increment of Serum VEGF Level and Catecholamine Cardiomyopathy - Kaneto, Hideaki; Kamei, Shinji; Tatsumi, Fuminori; Shimoda, Masashi; Kimura, Tomohiko; Nakanishi, Shuhei; Miyaji, Yoshiyuki; Nagai, Atsushi; Kaku, Kohei; Mune, Tomoatsu (Frontiers in Endocrinology, 2021)
Introduction Pheochromocytoma is a catecholamine-producing tumor in the adrenal medulla and is often accompanied by hypertension, hyperglycemia, hypermetabolism, headache, and hyperhidrosis, and it is classified as benign and malignant pheochromocytoma. In addition, persistent hypertension is often observed in subjects with malignant pheochromocytoma. Case Presentation A 52-year-old Japanese male was referred and hospitalized in our institution. He had a health check every year and no abnormalities had been pointed out. In addition, he had no past history of hypertension. In endocrinology markers, noradrenaline level was as high as 7,693 pg/ml, whereas adrenaline level was within normal range. Abdominal contrast-enhanced computed tomography revealed a 50-mm hyper-vascularized tumor with calcification in the right adrenal gland and multiple hyper-vascularized tumors in the liver. In 131I MIBG scintigraphy, there was high accumulation in the right adrenal gland and multiple accumulation in the liver and bone. In echocardiography, left ventricular ejection fraction was as low as 14.3%. In coronary angiography, however, there was no significant stenosis in the coronary arteries. Based on these findings, we finally diagnosed him as malignant pheochromocytoma accompanied by multiple liver and bone metastases and catecholamine cardiomyopathy. However, blood pressure was continuously within normal range without any anti-hypertensive drugs. Right adrenal tumor resection was performed together with left hepatic lobectomy and cholecystectomy. Furthermore, serum levels of vascular endothelial growth factor (VEGF) and parathyroid (PTH)-related protein were very high before the operation but they were markedly reduced after the operation. Conclusions This is the first report showing the time course of serum VEGF level in a subject with malignant pheochromocytoma, clearly showing that malignant pheochromocytoma actually secreted VEGF. In addition, this case report clearly shows that we should bear in mind once again that malignant pheochromocytoma is not necessarily accompanied by hypertension.